Spatially heterogeneous lithospheric architecture of the Cambay rift basin and adjoining Aravalli-Delhi Fold Belt, western India – A synthesis of magnetotelluric results - Nagarjuna, Danda; Kumar, Amit; Pavankumar, G.; Rao, C.K.; Manglik, Ajay (My University, 2023)
The Cambay rift basin (CRB) evolution has been associated with separation of the Indian continent from the African continent and subsequent interaction with the R´eunion mantle plume, which resulted in significant alternations in the regional lithospheric structure of western India, more prominently in the CRB due to its proximity to the plume track. In our continued effort to delineate the lithospheric structure of the CRB and adjoining regions, we acquired magnetotelluric (MT) data at 31 sites along a profile across the CRB and analyzed these. The 2D geoelectric model derived from this dataset reveals a collage of conductive and resistive formations. The resistive blocks indicate the Archaean lithosphere on the west, the uplifted crust within the CRB, and various structural units of the Precambrian Era on the east providing evidence for continuation of the Aravalli- Delhi Fold Belt trend beneath the CRB into Saurashtra. The conductive anomalies beneath the CRB infer the magmatic underplating associated with thermal influx derived from the upper mantle as a result of the R´eunion plume interaction. Integration of previous geophysical and present results infers a spatially heterogeneous lithosphere possibly representing an assemblage the Archaean and Proterozoic lithospheres beneath the CRB. The Proterozoic lithosphere is more vulnerable to the impact of the R´eunion plume due to its weak nature in comparison to the Archaean lithosphere. The Archaean lithosphere on the western side of CRB indicates initial stage of rifting, whereas Proterozoic lithosphere infers second stage coeval with the Deccan volcanic eruption. The heterogeneity in sedimentary thickness within the CRB spatially correlates with the contact of Archaean and Proterozoic lithospheres, which might have played a role in the formation of the basin structure, and sediment deposition.
Keywords: Cambay rift basin; Aravalli-Delhi Fold Belt; Magnetotellurics; Electrical conductivity; R´eunion plume